Relationships of physicians with pharmaceutical sales representatives and pharmaceutical companies: an exploratory study - Andaleeb, Syed Saad; Tallman, Robert F. (© 1996 Taylor & Francis Online, 2016)
This article was published in the Health Marketing Quarterly [© 1996 Taylor & Francis Online] and the definite version is available at : http://doi.org/10.1300/J026v13n04_07 The Journal's website is at: http://www.tandfonline.com/doi/abs/10.1300/J026v13n04_07